Chatbot-assisted therapy for patients with methamphetamine use disorder: a preliminary randomized controlled trial - Chun-Hung, Lee; Guan-Hsiung, Liaw; Wu-Chuan, Yang; Yu-Hsin, Liu (Frontiers in Psychiatry, 2023)
Background: Methamphetamine (MA) use disorder is associated with a large public health burden. Despite the therapeutic effects of psychosocial interventions based on current evidence, finding an approach to retain patients in treatment remains a real-world challenge. The rapid development of mobile health (mHealth) systems suggest the potential to provide real-time personalized care at any time and from any location, minimize barriers to treatment, maximize use, and promote the dissemination of accessible therapeutic tools in at-risk populations. The aim of our study was to investigate the feasibility and effectiveness of chatbots for the treatment of MA use disorder. Method: The inclusion criteria were (a) a diagnosis of MA use disorder as defined by the DSM-5, (b) age between 18 and 65 years, (c) no acute exacerbation of severe mental illness during initial assessment, such as schizophrenia or bipolar I disorder, (d) willingness to participate in standard outpatient treatment for ≥ 6 months, and (e) an Android phone. Participants were randomly allocated to either a chatbot–assisted therapy via smartphone (CAT) group or control group following simple randomization procedures (computerized random numbers) without blinding. All participants were followed up for 6 months. Treatment retention and monthly urine test results were analyzed as outcome measures. Results: Fifty and 49 participants were allocated to the CAT and control groups, respectively. There were no significant differences of retention time between the two treatment groups (df = 1, p = .099). The CAT group had fewer MA-positive urine samples than the control group (19.5% vs 29.6%, F = 9.116, p = .003). The proportion of MA-positive urine samples was positively correlated with frequency of MA use (r = .323, p = .001), severity of MA use disorder (r = 0.364, p < .001), and polysubstance use (r = .212, p = .035) and negatively correlated with readiness to change (r = -.330, p = .001). 55 participants completed the study at the 6-month follow up and 60% reported relative satisfaction. Conclusion: Participants in this study had favorable acceptance and gererally positive outcomes, which indicates that chatbot is feasible for patients who use MA.